Chronic kidney disease in European patients with obstructive sleep apnea: the ESADA cohort study. (18th May 2016) - Marrone, Oreste; Battaglia, Salvatore; Steiropoulos, Paschalis; Basoglu, Ozen K.; Kvamme, John A.; Ryan, Silke; Pepin, Jean‐Louis; Verbraecken, Johan; Grote, Ludger; Hedner, Jan; Bonsignore, Maria R.; ,
Summary: The cross‐sectional relationship of obstructive sleep apnea with moderate to severe chronic kidney disease, defined as an estimated glomerular filtration rate <60 mL min −1 ∙1.73 m −2, was investigated in a large cohort of patients with suspected obstructive sleep apnea studied by nocturnal polysomnography or cardiorespiratory polygraphy. Data were obtained from the European Sleep Apnea Database, where information from unselected adult patients with suspected obstructive sleep apnea afferent to 26 European sleep centres had been prospectively collected. Both the Modification of Diet in Renal Disease and the Chronic Kidney Disease‐Epidemiology Collaboration equations were used for the assessment of estimated glomerular filtration rate. The analysed sample included 7700 subjects, 71% male, aged 51.9 ± 12.5 years. Severe obstructive sleep apnea (apnea–hypopnea index ≥30) was found in 34% of subjects. The lowest nocturnal oxygen saturation was 81 ± 10.2%. Chronic kidney disease prevalence in the whole sample was 8.7% or 6.1%, according to the Modification of Diet in Renal Disease or the Chronic Kidney Disease‐Epidemiology Collaboration equations, respectively. Subjects with lower estimated glomerular filtration rate were older, more obese, more often female, had worse obstructive sleep apnea and more co‐morbidities ( P  < 0.001, each). With both equations, independent predictors of estimated glomerular filtration rate <60 were: chronic heart failure; female gender; systemic hypertension; older age; higher body mass index; and worse lowest nocturnal oxygen saturation. It was concluded that in obstructive sleep apnea, chronic kidney disease is largely predicted by co‐morbidities and anthropometric characteristics. In addition, severe nocturnal hypoxaemia, even for only a small part of the night, may play an important role as a risk factor for kidney dysfunction.